James Monroe - Gunderson, Megan M., 1981- (2017)
"This biography introduces readers to James Monroe including his military service, early political career, and key events from Monroe's administration including the Monroe Doctrine. Information about his childhood, family, personal life, and retirement years is included. A timeline, fast facts, and sidebars provide additional information. Aligned to Common Core Standards and correlated to state standards."--Publisher's website.
James Monroe -- Timeline -- Virginia childhood -- Joining the fight -- Politics and family -- Foreign relations -- Secretary of State -- President Monroe -- Going home -- Office of the President -- Presidents and their terms.
"The 5th president of the United States"--Cover.
Includes index.
Keywords: Monroe, James, -- 1758-1831 -- Juvenile literature; Monroe, James, -- 1758-1831.; Monroe, James, -- 1758-1831.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Presidents; United States; Biographies; Biography; Juvenile works; Biographies